Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.9790/4861-06315661
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of a novel crystal-barium malate trihydrate

Abstract: Barium malate trihydrate crystals are grown by limited diffusion technique in hydro-silica gel. Relevant functional groups are identified from the FT-IR spectrum. Single crystal XRD shows that the crystal system is monoclinic with space group P2 1 /n. The optical band gap of the material, estimated using DRS, is 1.028 eV. The material exhibits a three stage thermal decomposition pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…However, the water molecules in BaC 4 H 4 O 5 •3H 2 O make it has a lower stability temperature 130 °C. [38] The powder XRD patterns of the resultant compound shown in Fig. S2 have good agreement with the calculated XRD patterns from the single-crystal models confirming the structure.…”
Section: Accepted Manuscriptsupporting
confidence: 70%
“…However, the water molecules in BaC 4 H 4 O 5 •3H 2 O make it has a lower stability temperature 130 °C. [38] The powder XRD patterns of the resultant compound shown in Fig. S2 have good agreement with the calculated XRD patterns from the single-crystal models confirming the structure.…”
Section: Accepted Manuscriptsupporting
confidence: 70%
“…20 C]O asymmetric stretching vibration bands of the carboxylate group (carboxylic acid salt) are found in the interval between 1550 and 1600 cm À1 . The bands observed at 1427 or 1440 cm À1 can be attributed to the C-O symmetric stretching vibration of the carboxylate group, 11 but also to the dCH 2 mode of the methylene group 18,25 (a small contribution due to the presence of carbonate, calcium carbonate, cannot be fully withdrawn). The bands observed at 1391 and 1409 cm À1 can be related to the CH 3 asymmetric bending vibration (present in the lactate salt), but also to the C-O symmetric stretching vibration of the carboxylate group.…”
Section: Resultsmentioning
confidence: 99%
“…The bands observed at 1391 and 1409 cm À1 can be related to the CH 3 asymmetric bending vibration (present in the lactate salt), but also to the C-O symmetric stretching vibration of the carboxylate group. 18,25 The band observed between 1340 and 1350 cm À1 can be associated to the wagging of the CH 2 methylene group or to the CH 3 symmetric bending vibration (present in the lactate salt). The sharp bands at 1051 and 1103 cm À1 might be related to the C-O-stretching of the primary and secondary alcohols, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination of carboxylate ligand with various transition metals can lead to the formation of two and three dimensional complexes with an extensive network of hydrogen bonding and metal-metal interaction [16]. The structural investigations of complexes of carboxylic salts of transition metal ions are interesting because they exist in different structures and it is quite difficult to grow their crystals through the traditional slow cooling and slow evaporation methods [2,17]. Recently Mahalakshmi et al [4] reported polymeric structure of tetraaqua bismaleatocobalt (II) crystal grown by the controlled ionic diffusion in hydrosilica gel method which is analogue structure observed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Metal coordinated dicarboxyles related compounds have a significant role to play in materials science and technology due to their versatile applications in the field of hydrogen storage, magnetic properties, photoluminescence, photoconductivity, sensors and photoelectronics [1][2][3][4][5][6][7][8]. Recently, several researchers have shown keen interest in the growth and characterization of metal coordinated dicarboxylates.…”
Section: Introductionmentioning
confidence: 99%